2022
DOI: 10.3847/1538-4357/ac68f2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Disk-induced Apsidal Precession on Planets Captured into Mean Motion Resonance

Abstract: The process of migration into resonance capture has been well studied for planetary systems where the gravitational potential is generated exclusively by the star and planets. However, massive protoplanetary disks add a significant perturbation to these models. In this paper we consider two limiting cases of disk-induced precession on migrating planets and find that small amounts of precession significantly affect the equilibrium reached by migrating planets. We investigate these effects with a combination of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…By virtue of attempting to place model-independent constraints on these quantities through the kind of simplified parametric framework used in this study, we forego modeling the effects of physical phenomena, which are likely to play a role in shaping the early stages of giant planet evolution. For example, Murray et al (2022) found that disk precession could significantly alter resonance capture from the gas-free case and lead to larger amplitude libration-potentially paving the path toward easier instability triggering relative to the scenarios considered in this work. Additionally, chains of giant planets are likely to carve mutual gaps in a disk, the effect of which on planet-to-planet variations in the strength of eccentricity damping is still unclear, particularly in low-viscosity disks (Lega et al 2021;Griveaud et al 2023).…”
Section: Discussionmentioning
confidence: 91%
“…By virtue of attempting to place model-independent constraints on these quantities through the kind of simplified parametric framework used in this study, we forego modeling the effects of physical phenomena, which are likely to play a role in shaping the early stages of giant planet evolution. For example, Murray et al (2022) found that disk precession could significantly alter resonance capture from the gas-free case and lead to larger amplitude libration-potentially paving the path toward easier instability triggering relative to the scenarios considered in this work. Additionally, chains of giant planets are likely to carve mutual gaps in a disk, the effect of which on planet-to-planet variations in the strength of eccentricity damping is still unclear, particularly in low-viscosity disks (Lega et al 2021;Griveaud et al 2023).…”
Section: Discussionmentioning
confidence: 91%
“…This is because mean-motion resonances (MMRs), which we have ignored, could play an important dynamical role (see also the next paragraph), questioning the validity of secular approximation. For instance, for a Jupiter-mass planet, the nominal location of the 2:1 MMR -namely, a 2:1 = 2 2/3 a p (i.e., neglecting potential offsets due to the disk-induced precession; Murray et al 2022)-would be within the disk at a 2:1 /a in ≈ 1.07 if e p = 0.10 but at a 2:1  a in if e p = 0.30 (assuming M c = 1M e and using Equation (1) to relate a p and a in ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Murray et al (2022) demonstrated that if a resonant planet pair migrates into the cavity, the eccentricity of the inner planet can be excited to high values (e > 0.5) through disk-driven differential precession between the pair. In this scenario, the disk must be heavy enough to produce a high differential precession rate between the two planets in resonance, and the disk dispersal must proceed slowly enough to avoid destabilizing the resonant planet pair.…”
Section: Eccentricity Excitation Through Disk-planet Interactionsmentioning
confidence: 99%